Assessment of insect biodiversity in protected areas (Zoological Records and Reviews, 2022)
Protected areas (PAs) are the cornerstone of global biodiversity conservation strategy, yet the effectiveness of PAs insafeguarding insect diversity -- the most species-rich component of most terrestrial ecosystems -- remains poorlyevaluated relative to their well-studied role in vertebrate conservation. This study presents a comprehensive assessmentof insect biodiversity across 12 protected areas spanning three forest types in peninsular India -- the Eastern GhatsWildlife Sanctuary complex, the Nallamala Forest Reserve, and the Nagarjunasagar-Srisailam Tiger Reserve -- usingstandardised malaise trapping, light trapping, pitfall arrays, and vegetation sweeping at 64 survey stations over twosurvey seasons (2019-2021). A total of 1,284 insect species from 18 orders and 124 families are documented,representing the most comprehensive insect inventory for these protected areas to date. Coleoptera (342 species),Lepidoptera (284 species), Hymenoptera (218 species), and Diptera (196 species) are the most species-rich orders.Species richness is significantly higher in core zones compared to buffer zones of all assessed PAs (mean +28.4%), andhigher in PAs with lower surrounding human population density. Comparison with an unprotected forest control revealsthat PAs protect an estimated additional 184 insect species relative to equivalent unprotected forests. Twenty-eightspecies are new records for peninsular India. Twelve species are assessed as IUCN Threatened. The study confirms thesignificant but partial effectiveness of current PA management for insect conservation and identifies fire management,invasive species, and tourism pressure as priority management concerns.